Configurational theory and methods in organizational research - Fiss, Peer C.; Cambré, Bart; Marx, Axel (Emerald, 2013)
Some 20 years after the emergence of configurational theory as a key perspective in organization studies in the 1990s, this approach has yet to deliver on its promise. While we know that configurations the relative arrangement of parts and elements - matters, empirical research on configurations is just beginning to deliver on its promise.
Keywords: Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; Business mathematics & systems.; Organizational behavior -- Research -- Methodology.; elektronické knihy; electronic books